2007
DOI: 10.1111/j.1469-0691.2007.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal group C disease in Greece during 1993–2006: the impact of an unofficial single-dose vaccination scheme adopted by most paediatricians

Abstract: The aim of this study was to evaluate the impact of the meningococcal C conjugate vaccine on the epidemiology of meningococcal C disease in Greece. Data from the National Reference Laboratory for Meningococcal Disease and a questionnaire distributed to Greek paediatricians were assessed. Since the introduction of the vaccine in 2001, 72% of Greek paediatricians have administered it as one single dose to patients aged > or =12 months. This vaccination scheme has probably contributed to a dramatic decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…[11][12][13][14] As also observed by Mooney et al 14 , the reversal of the increasing trend of serogroup C related IMD was simultaneous with the timing of MCC introduction and, therefore, likely attributable to it. The impact of MCC was investigated in many other European and Italian regional studies [14][15][16][17][18][19][20][21][22][23][24][25] which showed an important decrease in N. meningitidis C related IMD and a vaccine effectiveness as high as 100% depending on the age group and on the time elapsed from vaccination. A downward trend in serogroup C related IMD was also confirmed by the European Center for Disease Prevention and Control (ECDC) in countries with MCC vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] As also observed by Mooney et al 14 , the reversal of the increasing trend of serogroup C related IMD was simultaneous with the timing of MCC introduction and, therefore, likely attributable to it. The impact of MCC was investigated in many other European and Italian regional studies [14][15][16][17][18][19][20][21][22][23][24][25] which showed an important decrease in N. meningitidis C related IMD and a vaccine effectiveness as high as 100% depending on the age group and on the time elapsed from vaccination. A downward trend in serogroup C related IMD was also confirmed by the European Center for Disease Prevention and Control (ECDC) in countries with MCC vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…3,34 This was until the introduction of the MenC vaccine which lead to serogroup B dominating and a decline in incidence in the 2000s. 6,19,41,42,72 The MenC vaccine was first introduced in 1999 in the United Kingdom and a 93% protective effect was found among teenagers in a study conducted the same year. 73 After one year of vaccination, the incidence of disease was observed to have reduced by 81% and herd immunity was induced 4,54,66,74 while carriage reduced by 66% from 1999 to 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Several countries have documented the effectiveness of meningococcal conjugate C vaccines; in particular, vaccination campaigns in the UK, Greece and Spain triggered a rapid decrease in cases of serogroup C disease [3,5,15]. However, there is also evidence that in the absence of vaccination disease incidence may fall as naturally acquired immunity rises [16,17] but this is not a rapid process [2,18].…”
Section: Discussionmentioning
confidence: 99%